(untitled) (Communications in Mathematical Research, 2021)
In this paper we give a strong converse inequality of type B in terms of unified K-functional K^α_λ (f, t^2) (0 ≤ λ ≤ 1, 0 < α < 2) for the Meyer-König and Zeller-Durrmeyer type operators.